IT CAPABILITY, IT GOVERNANCE, AND OPERATIONAL COST EFFICIENCY: EVIDENCE FROM INDONESIA - Aninda Puji Adila; Khalilul Rahman; Diva Trimuliani; Aditya Novsa Pratama (Bilancia : Jurnal Ilmiah Akuntansi, 2026)
This study aims to examine the relationship between Information Technology (IT) capability, IT governance, and operational cost efficiency in Indonesian organizations through a systematic literature review approach. Using the PRISMA protocol, the study analyzed 27 Scopus-indexed articles published between 2021 and 2026 that specifically addressed digital capability, governance mechanisms, and cost efficiency outcomes in Indonesia. The findings reveal that IT capability contributes significantly to operational efficiency when supported by mature IT governance structures, while governance acts as a critical moderator that aligns technological investments with organizational objectives and cost-control mechanisms. The study introduces a novel integrated framework that combines the Resource-Based View, Dynamic Capabilities Theory, and the Technology Productivity Paradox to explain how governance transforms digital resources into sustainable efficiency gains. The implications of this research suggest that organizations should strengthen governance practices alongside technological development to maximize the financial benefits of digital transformation and achieve long-term operational sustainability. Penelitian ini bertujuan untuk menganalisis hubungan antara kapabilitas teknologi informasi (TI), tata kelola TI, dan efisiensi biaya operasional pada organisasi di Indonesia melalui pendekatan systematic literature review. Dengan menggunakan protokol PRISMA, penelitian ini menganalisis 27 artikel terindeks Scopus yang diterbitkan pada periode 2021–2026 dan secara khusus membahas kapabilitas digital, mekanisme tata kelola, serta hasil efisiensi biaya di Indonesia. Hasil penelitian menunjukkan bahwa kapabilitas TI memberikan kontribusi yang signifikan terhadap efisiensi operasional apabila didukung oleh struktur tata kelola TI yang matang, sementara tata kelola berperan sebagai moderator penting yang menyelaraskan investasi teknologi dengan tujuan organisasi dan mekanisme pengendalian biaya. Kebaruan penelitian ini terletak pada pengembangan kerangka konseptual terintegrasi yang menggabungkan Resource-Based View, Dynamic Capabilities Theory, dan Technology Productivity Paradox untuk menjelaskan bagaimana tata kelola mengubah sumber daya digital menjadi efisiensi yang berkelanjutan. Implikasi penelitian menunjukkan bahwa organisasi perlu memperkuat praktik tata kelola bersamaan dengan pengembangan teknologi guna memaksimalkan manfaat finansial dari transformasi digital dan mencapai keberlanjutan operasional jangka panjang.